Analisis Pendapatan Petani Padi Organik dan Pendapatan Petani Non Organik Kecamatan Perbaungan Kabupaten Serdang Bedagai - Cemda, Abdul Rahman; Pirngadi, Rahmat Suryanto; Siregar, Aflahun Fadhly (Universitas Galuh, 2024)
Indonesia is a country with a tropical climate with a high level of soil fertility, making it possible to increase production results in the agricultural sector. The concept of sustainable agriculture is an environmentally friendly agricultural concept by prioritizing environmental, social and economic aspects. Perbauangan is one of the largest organic and non-organic rice producing sub-districts in Serdang Bedagai District, where currently many farmers have slowly switched to cultivating organic rice. The problem that will be examined in this research is to analyze the income of organic and non-organic rice in Serdang Bedagai District using a case study of Perbaungan SubDistrict. Lubuk Bayas village is the village that is the research site for analyzing the income of organic rice farmers, while Melati II village is the village that is the research site for analyzing the income of non-organic rice. The analytical model used to solve this problem is using income analysis with the equation